Caracterização de Efluente Têxtil e Proposta de Tratamento - Beltrame, Leocádia Terezinha Cordeiro (2000)
Textile industry deals with a high diversity of processes and generation of wastewaters with a high content of pollutant material. Before being disposed of in water bodies, a pre-treatment of the effluent is carried out, which is sometimes ineffective. In order to be properly treated, physical and chemical properties of the effluent must be known, as well as the pollutant agents that might be present in it. This has turned out to be a great problem in the textile industry, for there is a variety of processes and the pollutant load is very diversified. The characterization of the effluent allows the identification of most critical points and, as a consequence, the most appropriate treatment procedure to be employed, may be chosen. This study presents the results obtained after characterizing the effluent of a textile industry that comprises knitting, dyeing and apparel sections, processing mainly polyester/cotton articles. In this work, twenty samples of the effluent were collected, and related to the changes in production. From the results, a statistical evaluation was applied, determined in function of the rate of flow. The following properties and pollutants agents were quantitatively analysed: temperature; pH; sulfides; chlorine; alcalinity; chlorides; cianides; phenols; color; COD (Chemical Oxygen Demand); TOC (Total Organic Carbon); oil and grease; total, fixed and volatile solids; dissolved, fixed and volatile solids; suspended, fixed and volatile solids; setteable solids and heavy metals such as cadmium, copper, lead, chromium, tin, iron, zinc and nickel. Analyses were carried out according to ABNT NBR 13402 norm, based upon Standard Methods for the Examination of Water and Wastewater. As a consequence, a global treatment proposal is presented, involving clean production practices as contaminant load reducer, followed by conventional (biological) treatment